PENGARUH KOMPETENSI, MOTIVASI, LINGKUNGAN KERJA DAN PENGAWASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK MADYA MEDAN - Muhammad Joni Hidayat (Manajemen dan Bisnis, 2020)
The purpose of this study is to examine and explain how the influence of competence, motivation, work environment and work supervision on employee performance at the Medan Middle Tax Service Office. The research sample of 95 people. Based on the analysis results obtained there is a significant influence between competence on employee performance, because according to the results of the analysis of tcount t-table (2.862 1.67) at n = 95 with a significance level of 95%., There is a significant influence between motivation on employee performance, because the analysis results of tcount t-table (2.588 1.67) at n = 95 with a significance level of 95%, There is a significant influence between the work environment on employee performance, because according to the results of t-analysis t-table (2,046 1, 67) at n = 96 with a significance level of 95%, there is a significant influence between supervision on employee performance because according to the results of the analysis of t table t (1.794 1.67) at n = 96 with a significance level of 95%. count F table (109,995 2.48) with the numerator dk 4 and the number 90 denominator together (multiple) there is a positive and significant effect on competence, motivation, work environment, and supervision of the performance of employees of the Tax Office M adya Medan. Thus the hypothesis proposed is accepted.